Al-Alwani, Taha Jaber. “Qur’anic Concepts and Determining the Missions of the Prophets,” Year 9, Issues 33-34 (Summer-Fall 1424 AH/ 2003 CE), Pp. 11-46. - العلواني طه جابر (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma’rifah), 2003)
Taha Jaber al-Alwani’s article discusses a number of fundamental concepts, such as prophethood, the message, selection, and revelation, in an attempt to capture the boundaries in understanding them and to thus prevent Muslims from confusion in their religion as had happened with other peoples after the loss of their prophet, (e.g., as with those who idolized the graves of their prophets). The article aims to achieve an accurate perception of the role of these concepts and others in the building of the Islamic character, in mind and conscience, and to prevent confusion and disorder that creates divisions and factions among members of the Ummah (at times rendering one another as apostates without any valid or logical reason).